Determinants of Capital Structure: The Case of Turkish Hotels from Tourism Industry - Ahani, Maryam (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2015)
The aim of this study is to determine, investigate and describe the determinants of capital structure in the five major hotels, acting in the Tourism Industry of Turkey, over the period of 1998-2010. Different capital structure theories were probed with a view to establishing valid propositions concerning the determinants of capital structure of Turkish Hotels. The results have shown that size of the hotels, tangibility of their assets, risk level and non-debt tax shields can be considered as the major determinants of capital structure of hotels in Turkey. We found that the Trade-off theory seems to explain the choice of capital structure more appropriately, compared to other theories. Keywords: capital structure, determinants of capital structure, trade-off theory.

ÖZ: Bu çalışmanın amacı Türkiye turizm endüstrisinde faaliyet gösteren en büyük beş hotelin sermaye yapısı belirleyicilerini 1998-2010 yılları arasında incelemektir. Türk hotellerinin sermaye yapısı belirleyicileriyle ilgili geçerli önermeler elde etmek amacıyla çeşitli sermaye yapısı teorileri incelenmiştir. Yapılan analizler sonucunda Türkiye'de faaliyet gösteren hotellerin sermaye yapısı belirleyicileri hotel büyüklüğü, maddi varlıklar, risk seviyesi ve borç dışı vergi kalkanı olarak belirlenmiştir. Bulduğumuz sonuçlara göre dengeleme teorisi diğer teorilere kıyasla sermaye yapısını daha açık bir şekilde açıklamaktadır. Anahtar Kelimeler: sermaye yapısı, sermaye yapısı belirleyicileri, dengeleme teorisi.
Master of Science in Banking and Finance. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2015. Supervisor: Prof. Dr. Salih Katırcıoğlu
Keywords: Banking and Finance; Capital Structure - Tourism Industry - Hotels -Turkey; Capital structure; determinants of capital structure; trade-off theory